2007
DOI: 10.1073/pnas.0609973104
|View full text |Cite
|
Sign up to set email alerts
|

The 1′,4′-iminopyrimidine tautomer of thiamin diphosphate is poised for catalysis in asymmetric active centers on enzymes

Abstract: Thiamin diphosphate, a key coenzyme in sugar metabolism, is comprised of the thiazolium and 4-aminopyrimidine aromatic rings, but only recently has participation of the 4-aminopyrimidine moiety in catalysis gained wider acceptance. We report the use of electronic spectroscopy to identify the various tautomeric forms of the 4-aminopyrimidine ring on four thiamin diphosphate enzymes, all of which decarboxylate pyruvate: the E1 component of human pyruvate dehydrogenase complex, the E1 subunit of Escherichia coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
130
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(141 citation statements)
references
References 38 publications
11
130
0
Order By: Relevance
“…4A). The thiamin cofactor adopts the canonical V conformation juxtaposing the reactive C2 carbon of the thiazolium and the 4Ј-amino group of the pyrimidine ring, which acts as an intramolecular acid/base catalyst with high effective molarity and delicately balanced protonic equilibria (31)(32)(33). The isoalloxazine part of FAD is slightly bent over the N5-N10 axis (15°distortion), a structural feature that is thought to be beneficial for ET as this conformation resembles the reduced state of the flavin (27).…”
Section: Resultsmentioning
confidence: 99%
“…4A). The thiamin cofactor adopts the canonical V conformation juxtaposing the reactive C2 carbon of the thiazolium and the 4Ј-amino group of the pyrimidine ring, which acts as an intramolecular acid/base catalyst with high effective molarity and delicately balanced protonic equilibria (31)(32)(33). The isoalloxazine part of FAD is slightly bent over the N5-N10 axis (15°distortion), a structural feature that is thought to be beneficial for ET as this conformation resembles the reduced state of the flavin (27).…”
Section: Resultsmentioning
confidence: 99%
“…Interpretation of our results is aided by our assignment of a negative CD band centered near 320-330 nm to (i) the 4Ј-aminopyrimidine tautomer of ThDP (AP form in SI Scheme I; ref. 8) or (ii) the Michaelis complex (MC) formed with either substrate (9) or substrate analogue MAP (9,10). We have shown that on E1ec, it is difficult to observe the AP form.…”
Section: Loop Dynamics Influences Covalent Addition Of the Substrate mentioning
confidence: 98%
“…After 45 min, samples were centrifuged for 10 min at 17,530 ϫ g, and the subcomplex was applied to the column. Circular dichroism (CD) experiments were carried out on an Applied Photophysics Chirascan spectrometer (Leatherhead, UK) at 30°C as reported earlier from our laboratories (8,10,20).…”
Section: Interaction Of E1ec and Its Variants With E2ec Monitored By mentioning
confidence: 99%